Are the Targets of the Nature Restoration Regulation Achievable at a Regional Scale? An Analysis of Natura 2000 Sites on the Island of Sardinia - Michele Defraia; Erika Bazzato; Michela Marignani (Environmental Management, 2025)
The Nature Restoration Regulation (NRR) aims to restore 20% of degraded terrestrial and marine ecosystems across Europe by 2030. One of the initial provisions states that, by 2030, Member States should prioritize the restoration of natural ecosystems within Natura 2000 sites, emphasizing the urgency of assessing the conservation status of habitats in these areas. We selected Sardinia as a case study to evaluate the feasibility of the NRR at the regional level. The Natura 2000 sites in Sardinia cover a comparable percentage of territory (18.87%) to the national (19.38%) and European level (18.6%). Additionally, Sardinia’s insularity, high biodiversity levels, and low population density make it an ideal model for testing restoration strategies. Using official Natura 2000 data provided by the Italian Ministry of the Environment, we assessed the potential for restoration for each habitat within each site based on the conservation status values. The results indicated that coastal ecosystems were the most endangered. However, their limited distribution meant that their restoration would have a modest impact on achieving the NRR target. In contrast, forest and shrub habitats, which were more widely distributed, emerged as the main contributors to the restoration goals. Conducting this study at a regional level allowed us to provide actionable recommendations for management practices to be locally adopted. Our findings confirmed that restoration efforts confined to Natura 2000 sites alone would be insufficient to meet the NRR targets, underscoring the need to implement additional restoration measures in agricultural, urban, and other natural and semi-natural areas.